Restorative Hand Therapy Exercise using IoT-Based Flex Force Smart Glove - Chang, Yi Neng; Ishak, Mohamad Khairi; Ammar, Khalid (Makara Journal of Technology, 2023)
Stroke has long been a major health concern in Malaysia, with cerebrovascular disease accounting for one-third of all deaths. Patients who have had a stroke have varying degrees of movement impairment, which can be improved with physiotherapy. A smart glove system is proposed in this paper to measure and visualize patient finger flexes in real-time remotely and record these flexes for further analysis to monitor and assess patient physiotherapy sessions. The system is designed to help physiotherapists evaluate physiotherapy exercises of patients and provide detailed information regarding the rehabilitation process. This paper also includes performance analysis and data from physiotherapy sessions using the system. Overall, the flex force smart glove shows promise in aiding restorative hand therapy exercises.